Mechanical characterization of lattice structures fabricated by selective laser melting via an image-based finite cell method with a damage model - Zhang, Biao; Lian, Yanping; Li, Ming-Jian; Wang, Chunpeng; Gao, Ruxin (Materials & design, 2024)
Lattice structures fabricated by the selective laser melting (SLM) additive manufacturing process hold great potential for diverse applications. However, their actual mechanical behaviors often deviate from their counterparts with the as-designed geometries due to manufacturing defects. In this study, we presented an in-depth mechanical characterization of imperfect octet lattice structures via an image-based finite cell method (FCM) in combination with the multi-level hp refinement scheme for resolving the local defects and a Lemaitre damage model to conduct the damage analysis. Micro-computed tomography scanning was utilized to scan six SLM-fabricated octet lattice cells to obtain their as-built geometries. Based on the obtained geometry, the force-displacement curves and the damage distribution of the octet lattice cells and struts under given loads were predicted. The numerical results indicate that external defects significantly affect the struts' damage distribution, while internal voids have a lesser influence due to their low volume fraction. It is identified that the SLM-fabricated octet lattice cell presents better elastoplastic behavior along the loading direction perpendicular than parallel to its build direction. These insights into the mechanical performance of imperfect octet lattice cells underscore the defects' adverse effects and advance the understanding of their significance in SLM components. •Image-based multi-level hp finite cell method with Lemaitre's damage model is presented.•Damage distribution and force-displacement curves of the imperfect octet lattice cells and struts are predicted.•External defects significantly influence the damage distribution of the as-built strut.•Fabricated octet lattice cell exhibits loading direction-dependent mechanical behaviors.